(untitled) (Archives of Mechanics - Test, 2015)
This paper concerns the mathematical and numerical modelling of thermal phenomena and phase transformations in the solid state accompanying laser heating processes. Thermal phenomena with the motion of a liquid metal in the fusion zone are analyzed on the basis of numerical solution of equations for mass, momentum and energy conservation. Phase transformations in solid state are estimated using classic models of the kinetics of phase transformations as well as continuous heating transformations (CHT) and continuous cooling transformations (CCT) diagrams for S355 steel. Computer simulations are executed for the laser welding process in order to predict the influence of welding speed on the structural composition as well as thermal and structural strains in the joint.